Morphology and connections of intratrigeminal cells and axons in the macaque monkey - Susan eWarren; Paul J eMay; Paul J eMay; Paul J eMay (Frontiers Media S.A., 2013)
Trigeminal primary afferent fibers have small receptive fields and discrete submodalities, but second order trigeminal neurons often display larger receptive fields with complex, multimodal responses. Moreover, while most large caliber afferents terminate exclusively in the principal trigeminal nucleus, and pars caudalis of the spinal trigeminal nucleus receives almost exclusively small caliber afferents, the characteristics of second order neurons do not always reflect this dichotomy. These surprising characteristics may be due to a network of intratrigeminal connections modifying primary afferent contributions. This study characterizes the distribution and morphology of intratrigeminal cells and axons in a macaque monkeys. Tracer injections centered in the principal nucleus and adjacent pars oralis retrogradely labeled neurons bilaterally in pars interpolaris, but only ipsilaterally, in pars caudalis. Labeled axons terminated contralaterally within pars interpolaris and caudalis. Features of the intratrigeminal cells in ipsilateral pars caudalis suggest that both nociceptive and non-nociceptive neurons project to principalis. A commissural projection to contralateral principalis was also revealed. Injections into pars caudalis labeled cells and terminals in the principal nucleus and pars oralis on both sides, indicating the presence of bilateral reciprocal connections. Labeled terminals and cells were also present bilaterally in pars interpolaris and in contralateral pars caudalis. Interpolaris injections produced labeling patterns similar to those of pars caudalis.Thus, the rostral and caudal poles of the macaque trigeminal complex are richly interconnected by ipsilateral ascending and descending connections providing an anatomical substrate for complex analysis of oro-facial stimuli. Sparser reciprocal crossed intratrigeminal connections may be important for conjugate reflex movements, such as the corneal blink reflex.